Evaluation of the use of Court Video Conference Hearings in Angeles City, Philippines - Pangan, Mark John M.; Dausan, Alrien F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The COVID-19 pandemic prompted courts worldwide to swiftly transition to online operations, including virtual hearings, to maintain continuity amid health concerns. This shift signifies a lasting impact on the justice system. Despite this, research on the effectiveness and challenges of court videoconferencing, particularly in the Philippines, remains limited. This study aimed to address this gap by employing a descriptive-evaluative approach and surveying 213 respondents, including court officers, prosecutors, lawyers, jail officers, and police officers, in Angeles City. The study assessed challenges such as procedural integrity and technical glitches, as well as perspectives on judicial efficiency and cost effectiveness. Findings revealed significant hurdles in videoconference hearings, yet respondents recognized their benefits in expediting case resolutions and enhancing security. Interestingly, there was no significant difference in evaluations across respondent groups. Interviews corroborated survey results, highlighting concerns and benefits of videoconference hearings. Addressing challenges while leveraging benefits is crucial, requiring investment in technological literacy, internet connectivity, and procedural integrity safeguards. Policymakers should also explore solutions to infrastructure limitations, fostering widespread adoption of videoconference hearings for a more effective and fair legal system.